Exploring the Role of the Built and Social Neighborhood Environment in Moderating Stress and Health - Matthews, Stephen A. (2010)
BACKGROUND: Health researchers have explored how different aspects of neighborhood characteristics contribute to health and well-being, but current understanding of built environment factors is limited. PURPOSE: This study explores whether the association between stress and health varies by residential neighborhood, and if yes, whether built and social neighborhood environment characteristics act as moderators. METHODS: This study uses multilevel modeling and variables derived from geospatial data to explore the role of neighborhood environment in moderating the association of stress with health. Individual-level data (N=4,093) were drawn from residents of 45 neighborhoods within Philadelphia County, PA, collected as part of the 2006 Philadelphia Health Management Corporation's Household Health Survey. RESULTS: We find that the negative influence of high stress varied by neighborhood, that residential stability and affluence (social characteristics) attenuated the association of high stress with health, and that the presence of hazardous waste facilities (built environment characteristics) moderated health by enhancing the association with stress. CONCLUSIONS: Our findings suggest that neighborhood environment has both direct and moderating associations with health, after adjusting for individual characteristics. The use of geospatial data could broaden the scope of stress–health research and advance knowledge by untangling the intertwined relationship between built and social environments, stress, and health. In particular, future studies should integrate built environment characteristics in health-related research; these characteristics are modifiable and can facilitate health promotion policies.